MANUFACTURER PRICE SURVEY COOPERATION OF THE REPRESENTATIVE OFFICE OF BANK INDONESIA (BI) LHOKSEUMAWE & FACULTY OF ECONOMICS AND BUSINESS MALIKUSSALEH UNIVERSITY – JUNE 2024 - Muammar Khaddafi; Chalirafi; Mohd Heikal; Munandar; Rico Nur Ilham; Thasrif Murhadi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
The development of the Strategic Food Price Information Center (PIHPS) is a real effort from the TPID Pokjanas to facilitate the development of a food information system which also functions as a national scale food price control policy coordination system. PIHPS aims to be a price monitoring tool, policy coordination and a means to expand access to price information for the public. Currently, the information in the National PIHPS focuses on 10 food commodities that dominantly contribute to inflation. Data were collected from direct surveys in 164 traditional markets from 82 CPI inflation sample cities covering 34 provinces with a standardized methodology. Apart from traditional markets, in 2017 development was carried out for modern market price data and large trader data. The target respondents are producers, namely companies/industry/agricultural farmer households/farmer group associations that produce goods. The price data collected is producer price data which includes tax and the enumerated data is point-in time data. The output of observations produced by surveyors is in the form of food price data, names, addresses, contacts (cellphone numbers) of respondents for the commodities surveyed along with the quality of the commodities. Accompanied by photo data of the respondent with the surveyor, and business photos (commodities produced)